Enhancing the Emergency Financing Toolkit-Responding To The COVID-19 Pandemic. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2020)
The COVID-19 pandemic is taking a human toll and has unleashed a series of shocks on the Fund's entire membership, creating severe disruption in the global economic and financial system. As a result, many emerging market and developing country (EMDC) members face urgent and unprecedented financing needs, creating significant immediate demand for Fund resources. In order to respond to members' large and urgent financing needs, the paper proposes to enhance the Fund's emergency financing toolkit, through a temporary increase in access limits for both the Rapid Financing Instrument (RFI), available to all members, and the Rapid Credit Facility (RCF), available to Poverty Reduction Growth Trust-eligible members only. It is proposed to increase these access limits for a proposed period of six months, which may be extended by the Executive Board. A companion Board paper sets out proposals to accelerate Board consideration of member requests for financing under the RCF and RFI, completion of reviews and requests for changes in access in existing arrangements, and requests for grant assistance under the Catastrophe Containment and Relief Trust.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet